Managerial Recommendations for Enhancing Green Consumption Behavior and Sustainable Consumption - Nga, Lu Phi; Tam, Phan Thanh (Ital Publication, 2024)
The green consumerism movement is gaining steam in emerging nations with middle-income or higher populations, such as Vietnam, and is particularly well-liked in affluent countries. In addition, the importance of green consumerism is gaining significant traction, alongside efforts to promote ecologically friendly production and consumption. As the economy progressed, people's living standards improved, leading to a growing need for high-quality, safe products and services. This is particularly true for items that directly serve people and contribute to their everyday lives. Therefore, the article aims to evaluate the factors affecting green consumer behavior and sustainable consumption based on the structural equation model with the least squares method to test their hypotheses. The data were applied in the study through a survey of 360 consumers in 04 big cities in Vietnam. Research results showed that seven factors impact green consumption behavior, including (1) environmental awareness, (2) green product characteristics, (3) green marketing, (4) perceptions about green product prices, (5) social influence, (6) environmental policy, and (7) green consumption policy with significance 0.01. The finding explores green consumption behavior influencing sustainable consumption with a significance of 0.01. The practical implication helps managers, policymakers, and manufacturers consider applications to improve humanity and behavior green consumption in the global context of moving towards sustainable green development. The theory implication is to change behavior to improve greening production, reduce pollution and greenhouse emissions, and move towards sustainable development, bringing many practical economic and social benefits and intangible value for businesses. Simultaneously, the novelty of the study aids enterprises in staying abreast of this trend, enabling them to seize possibilities for fast growth, extend their market presence, and capitalize on governmental backing for businesses. Doi: 10.28991/ESJ-2024-08-06-07 Full Text: PDF